Differences and significance of peripheral blood interleukin-6 expression between patients with granulomatous lobular mastitis and those with benign breast tumors - Zhou, Yue; Wu, Jingjing; Ma, Lina; Wang, Bing; Meng, Tian; Chen, Hongfeng; Ye, Meina (Frontiers in Medicine, 2023)
Objective It is unclear whether the mechanism of the interleukin (IL)-6 signaling pathway is similar between granulomatous lobular mastitis (GLM) and benign breast tumors. This study aimed to explore the differences and significance of peripheral blood IL-6 and related cytokines, routine blood test results, and C-reactive protein (CRP) levels between patients with GLM and benign breast tumors. Methods Seventy-three inpatients with GLM who underwent surgery and 60 patients with benign breast tumors diagnosed based on pathological findings between November 2022 and May 2023 were included. The white blood cell (WBC) and neutrophil (NEU) counts were determined using an automatic blood cell analyzer, the CRP level was determined by an immunoturbidimetric assay, and serum IL-6 and related cytokine levels were determined by an enzyme-linked immunosorbent assay. Results The WBC, NEU, and CRP values in patients with GLM were significantly higher than those in patients with benign breast tumors (P < 0.01). Serum IL-6 levels were significantly higher in patients with GLM than in those with benign breast tumors (P < 0.01). There were no significant differences in the serum concentrations of IL-1β, IL-7, and interferon (IFN)-γ between patients with GLM and those with benign breast tumors (P > 0.05), but the tumor necrosis factor (TNF)-α level was higher in patients with GLM than in those with benign breast tumors (P < 0.01). In patients with GLM, the Pearson correlation analysis showed that the IL-6 level was positively correlated with NEU, NEU%, CRP, IL-17, and TNF-α values (P < 0.01). Additionally, the IL-6 level was weakly positively correlated with WBC and IFN-γ values. Conversely, in patients with benign breast tumors, the IL-6 level was not significantly correlated with the aforementioned indicators in routine blood tests but was positively correlated with IL-17, IFN-γ, and TNF-α values (P < 0.01). Conclusions IL-6, NEU, NEU%, and CRP values were significantly elevated in patients with GLM compared to those with benign breast tumors, indicating that IL-6 plays an important role in the development and onset of GLM. The correlation between these cytokines and the development and progression of benign breast tumors needs to be further explored, as cytokines such as IL-6 may provide effective markers for the treatment of GLM.